(untitled) (Olhares, 2015)
The table work as a fase destined to the scenic preparation. Place for observations and creation of aesthetic potentialities. The collective analysis of the dramatic text. Mediation place destined to the search for a deeper dramatic construction of the text and a closer personal bond between the creation team and the cast. Brief reflection of the primer actions for the theatric construction and its emphasis: text or scene? The table work stressing the reflexive practice of the montage.